2014
DOI: 10.1111/j.1548-2456.2014.00234.x
|View full text |Cite
|
Sign up to set email alerts
|

Countering Convergence: Agency and Diversity Among Guatemalan NGOs

Abstract: The proliferation of nongovernmental organizations across the developing world has sparked discussions of the “NGOization” of civil society and concern that NGOs have become increasingly uniform and internally homogenous. This article explores the evolution of NGOs in Guatemala since the 1960s and finds that NGOs historically and currently respond in diverse ways to external pressures—adjusting their strategies and actively attempting to shape their environment. Comparing two microcredit NGOs, it finds in addi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 25 publications
0
7
0
Order By: Relevance
“…One overlooked effect of untrained actors, like volunteers and nonprofit workers, working together is they momentarily avoid the professionalization that occurs in social movements or nonprofits (Alvarez 1999;Mawdsley, Townsend, and Porter 2005;Andrews 2014;Beck 2014). Katz analyzed the effects of professionalization in NGOs and found that professionalization "compromises more radical agendas and blunts the power of opposition" (Katz 2005, 627).…”
Section: Nonprofit Workersmentioning
confidence: 99%
“…One overlooked effect of untrained actors, like volunteers and nonprofit workers, working together is they momentarily avoid the professionalization that occurs in social movements or nonprofits (Alvarez 1999;Mawdsley, Townsend, and Porter 2005;Andrews 2014;Beck 2014). Katz analyzed the effects of professionalization in NGOs and found that professionalization "compromises more radical agendas and blunts the power of opposition" (Katz 2005, 627).…”
Section: Nonprofit Workersmentioning
confidence: 99%
“…Nonprofit sector research is currently characterized by a one-way conversation obscuring or ignoring the voices of native/indigenous leaders. This problem has been acknowledged in the field as nonprofit scholars comment on the general lack of native/indigenous voices, either local or international (sometimes referred to as grassroots voices), in the research produced (Beck, 2014;Pallas, Gethings, Harris, 2014). One argument posits burying occurs because of sector NGOization, professionalization, managerialism, etc.…”
Section: Statement Of Problemmentioning
confidence: 99%
“…One argument posits burying occurs because of sector NGOization, professionalization, managerialism, etc. (Alvarez, 1999;Beck, 2014;Chowdhury, 2011) describing the modern nonprofit management and leadership environment (Salamon, 2012). Defining native/indigenous broadly as individuals native to a particular country outside North America and Europe, an extensive search of the scholarship mirrored the concern of Beck (2014) and Pallas, Gethings, and Harris (2014).…”
Section: Statement Of Problemmentioning
confidence: 99%
See 2 more Smart Citations